Phytochemical Analysis, In-vitro, and In-silico Antibacterial Activity of Stembark Extract of Anogeissus leiocarpus (DC) Guill and Perr (Sciences of Pharmacy, 2023)
Bacterial infections subsequently leading to antibiotic resistance has been a leading cause of mortality and morbidity worldwide especially in developing countries with high poverty rate and poor healthcare system. Thus, prompting the prospect in alternative therapy such as medicinal plants. In the present study, we evaluated the antibacterial action of stem bark extract of Anogeissus leiocarpus (AL) Guill and Perr. as applied in folkloric medicine for antibacterial purposes. The phytochemicals present in the plant extract were identified and quantified, followed by the determination of the antibacterial effects of the extract against Escherichia coli and Staphylococcus aureus. Molecular docking study was carried out to ascertain the inhibitory effects of compounds from AL against bacterial enzymes. Alkaloids (7.17% ±0.60), saponins (11.33% ±3.18), and flavonoids (31.01% ±4.04) were detected. A maximum ZI was observed for E. coli compared to S. aureus at the highest extract concentration (100 mg/mL) with amoxicillin having superior ZI at 50 mg/mL concentration. The MIC against E. coli and S. aureus were 12.5 mg/mL and ≤ 6.25 mg/mL respectively while the MBC was>100 mg/mL and 100 mg/mL respectively. Among the identified compounds, IX exhibited the least binding affinity (BA) (7.2 kcal/mol) and inhibition constant (Ki) (5 µM) against UDP-N-acetylglucosamine Enolpyruvyl Transferase (Mur A) compared to all the other targets. AL demonstrated antibacterial activity evidenced by the bacterial growth inhibition, bactericidal potential, and in-silico study revealing high affinity of the bacterial enzymes for the identified compounds, thereby supporting the acclaimed antibacterial use of the plant in folkloric medicine.